Mecanismos de explotación sexual de niñas y adolescentes en los alrededores del puerto fluvial de Pucallpa - Mujica, Jaris (2011)
The sexual exploitation of children and adolescents is a phenomenon that has grown with the expansion of extractive industries (timber, oil, minerals and gas) in the Peruvian Amazon. The article is part of a long research in the city of Pucallpa and the route north of the Ucayali River. Its central objective is to demonstrate the economic dynamics of the mechanisms of commercial sexual exploitation of children and adolescents around the river port. We study the mechanisms of exploitation of local bars and restaurants in the port, the demand and perceptions of sexual exploitation of children, and the economic logic of this phenomenon. This is a business attached to the trade in alcoholic beverages and food, and not due to an organized criminal logical, but to a familiar system of exploitation.